Manajemen Anestesi pada Seksio Sesaria Emergensi dengan Kelainan Faktor Koagulasi - Uyun, Yusmein; Apsari, Ratih Kumala Fajar; Hendra, Maijoni (Jurnal Komplikasi Anestesi, 2020)
The selection of anesthesia techniques for caesarian section is determined by various factors, namely the indication of the operation, the choice of the patient and surgeon, and the technical ability (skill) of the surgeon. Clinical evaluation of patients with coagulopathy is very important to determine the anesthetic technique. Clinical evaluation must be individualized, taking into account the risks and benefits of anesthesia techniques. The risk of spinal hematoma or epidural in patients has not been completely eliminated, but it remains a factor that must be considered individually in determining whether neuraxial anesthesia is appropriate for that patient.